2017
DOI: 10.18632/oncotarget.14721
|View full text |Cite
|
Sign up to set email alerts
|

Variants in ANRIL gene correlated with its expression contribute to myocardial infarction risk

Abstract: ANRIL (antisense non-coding RNA in the INK4 locus), located at the 9p21.3 locus, has been known to be closely associated with the risk of coronary artery disease (CAD). To date, studies of the 9p21.3 variants on CAD risk mainly focus on the non-coding region of ANRIL. However, the biological significance of the variants on ANRIL promoter and exons is still unknown. Here we investigate whether the variants on ANRIL promoter and exons have an effect on myocardial infarction (MI) risk, and further analyze the ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
37
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(40 citation statements)
references
References 41 publications
(66 reference statements)
3
37
0
Order By: Relevance
“…[32][33][34] Additionally, the variants on ANRIL promoter and exons associated with ANRIL expression contribute to the risk of myocardial infarction. 35 In the present study, our data supported that ANRIL was downregulated in the serum of AMI patients, consistent with a previous work. 6 Moreover, we veried that H/R treatment time-dependently decreased ANRIL expression in myocardial cells.…”
Section: Discussionsupporting
confidence: 93%
“…[32][33][34] Additionally, the variants on ANRIL promoter and exons associated with ANRIL expression contribute to the risk of myocardial infarction. 35 In the present study, our data supported that ANRIL was downregulated in the serum of AMI patients, consistent with a previous work. 6 Moreover, we veried that H/R treatment time-dependently decreased ANRIL expression in myocardial cells.…”
Section: Discussionsupporting
confidence: 93%
“…More recently, a consistent association between two variants in the 9p21.3 locus (rs10965215 and rs10738605) and CAD has been reported also in the Chinese Han population (Cheng et al, 2017 ). For rs10965215, unconditional logistic regression analysis revealed that the G allele increased MI risk with OR of 1.37 (95% CI = 1.05–1.78, P = 0.020).…”
Section: Genetic Variants In Inflammatory Genes and Coronary Artery Dmentioning
confidence: 72%
“…For rs10965215, unconditional logistic regression analysis revealed that the G allele increased MI risk with OR of 1.37 (95% CI = 1.05–1.78, P = 0.020). For rs10738605, C allele conferred increased MI risk with OR of 1.38 (95% CI = 1.06–1.80, P = 0.019) as compared to the G allele after adjustment for conventional risk factors (Cheng et al, 2017 ).…”
Section: Genetic Variants In Inflammatory Genes and Coronary Artery Dmentioning
confidence: 99%
“…The majority of SNP in the ANRIL gene were located in intronic regions, but recently two exonic variants were reported to be associated with MI. Sequencing of the promoter region and UTR upstream of ANRIL showed no variant significantly associated with MI [138]. Some other studies investigating the effects of 9p21.3 variants on expression and regulation of 9p21.3 genes indicated that rs1333049 altered the expression of CDKN2A/B and ANRIL.…”
Section: Discussionmentioning
confidence: 93%